Analisis Permasalahan Pembangunan Infrastruktur Jalan: Studi Kasus Perencanaan dan Pelaksanaan di Provinsi Papua Barat - Andi Setyo Pambudi; Sri Hidayati; Bambang Pramujo (Publisia: Jurnal Ilmu Administrasi Publik, 2022)
Roads are the fastest growing infrastructure compared to other infrastructure in various countries, including Indonesia. The road sector requires high investments to meet national development targets. For both local and central governments, infrastructure development should be a shared concern from planning to implementation. Specific transfer fund policies such as the Physical DAK (Special Allocation Funds) are an opportunity for regions to build road infrastructure better. This study aims to show the top-down and bottom-up planning portrait for the Physical DAK Road Sector and analyze field problems that have been strategic issues for regional development in the road infrastructure field. This study also shows the road infrastructure development problem through site visits to the sample locations, which the Papua Barat Province selected as one of the largest recipients of the DAK Physical budget in Indonesia. The research method uses a mixed-method approach through gap analysis based on literature studies of RKP (Government Work Plan) and RKPD (Local Government Work Plan) in 34 provinces in Indonesia, questionnaires, and site visits. Based on the planning gap analysis results (RKP-RKPD in all the provinces throughout Indonesia), only 3 (three) provinces did not include the Road Sector activity menu from the DAK allocation in their RKPD, namely Papua Barat, Sulawesi Tengah, and Sumatera Utara. The analysis results also show that 24 provincial RKPDs are 100 percent following the DAK content in the RKP, 5 (five) provinces only set 66 percent, and 2 (two) of the province set 33 percent. In the case study location in Papua Barat related to Physical DAK for Road Sector Assignments context, the Papua Barat RKPD document in 2019 does not yet fully have a specific plan following the DAK activity menu. In the implementation aspect, there were also many problems related to regulation and governance that required more attention, both top-down and bottom-up.